High resolution FTIR study of the ν7+ν10-ν10 and ν10+ν12-ν10 "hot" bands of C2H4 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Onopenko G. A.; Aslapovskaya Yu. S. Yuliya Sergeevna; Gericke K.-H.; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann; Horneman V.-M. (2014, 2014)
Title screen